The Liverpool Care Pathway for cancer patients dying in hospital medical wards: A before–after cluster phase II trial of outcomes reported by family members. (January 2014) - Costantini, Massimo; Pellegrini, Fabio; Di Leo, Silvia; Beccaro, Monica; Rossi, Carla; Flego, Guia; Romoli, Vittoria; Giannotti, Michela; Morone, Paola; Ivaldi, Giovanni P; Cavallo, Laura; Fusco, Flavio; et al.
Background: Hospital is the most common place of cancer death but concerns regarding the quality of end-of-life care remain. Aim: Preliminary assessment of the effectiveness of the Liverpool Care Pathway on the quality of end-of-life care provided to adult cancer patients during their last week of life in hospital. Design: Uncontrolled before–after intervention cluster trial. Settings/participants: The trial was performed within four hospital wards participating in the pilot implementation of the Italian version of the Liverpool Care Pathway programme. All cancer patients who died in the hospital wards 2–4 months before and after the implementation of the Italian version of Liverpool Care Pathway were identified. A total of 2 months after the patient's death, bereaved family members were interviewed using the Toolkit After-Death Family Interview (seven 0–100 scales assessing the quality of end-of-life care) and the Italian version of the Views of Informal Carers - Evaluation of Services (VOICES) (three items assessing pain, breathlessness and nausea-vomiting). Results: An interview was obtained for 79 family members, 46 (73.0%) before and 33 (68.8%) after implementation of the Italian version of Liverpool Care Pathway. Following Italian version of Liverpool Care Pathway implementation, there was a significant improvement in the mean scores of four Toolkit scales: respect, kindness and dignity (+16.8; 95% confidence interval = 3.6–30.0; p = 0.015); family emotional support (+20.9; 95% confidence interval = 9.6–32.3; p < 0.001); family self-efficacy (+14.3; 95% confidence interval = 0.3–28.2; p = 0.049) and coordination of care (+14.3; 95% confidence interval = 4.2–24.3; p = 0.007). No significant improvement in symptom' control was observed. Conclusions: These results provide the first robust data collected from family members of a preliminary clinically significant improvement, in some aspects, of quality of care after the implementation of the Italian version of Liverpool Care Pathway programme. The poor effect for symptom control suggests areas for further innovation and development.